Subsurface Structural Modelling using the Gravity Method in the Pacitan Area, Indonesia based on Derivative Analysis and Model Inversion (Rudarsko-geološko-naftni zbornik, 2025)
The southern part of Java is dominated by volcanoes covered by thick and young volcanic deposits. Due to the complex subsurface conditions, active geophysical techniques such as seismic reflection cannot be used in this volcanic area. However, the gravity method provides a suitable alternative for geophysical exploration in this challenging environment. Gravity data obtained from satellite measurements was used to create Bouger anomaly maps to overcome this. Structural analysis in this research used derivative analysis, namely, first and second horizontal derivatives. The modelling was done using an inverse model, and the inversion process was carried out using the SVD and Occam methods. In conducting the structural analysis and inversion model, the data used is residual anomaly data obtained from the complete Bouger anomaly by carrying out the previous bandpass filter. The research produces a subsurface model detailing the geological features of the study area, including the basin and structural formations.Two cross-sections, A-A' and B-B', were created to interpret the geological model from north-south and west-east directions. The formations and values of both density and density contrast found in the study area according to rock age from old to young are the Arjosari Formation (-0.3 - -0.28 gr/cm3), the Mandalika Formation (-0.28 - -0.25 gr/cm3), Intrusion (0.25 – 0.4 gr/cm3), the Jaten Formation (-0.1 – 0.25 gr/cm3), the Wuni Formation (-0.25 - -0.2 gr/cm3), and the Nampol Formation (-0.2 - -0.1 gr/cm3). These revealed six rock formations in cross-section A-A' and three rock formations in cross-section B-B'. The density values of various formations were also determined. The reverse faults, strike-slip faults, and normal faults were the geological structures found. The analysis also identified two sedimentary basins, the Wonogiri basin and the Pacitan basin, with a depiction of the Pacitan sub-basin in the B-B' section.